How to Sell a Book? Insights from Romania - ZBUCHEA, Alexandra; HRIB, Bogdan (Management Dynamics in the Knowledge Economy, 2019)
Many other famous intellectuals, artists and writers stress various positive aspects of reading. Scientific research in medicine and psychology also prove the positive outcomes of reading. Therefore, it is not a surprise that books are highly valued by societies. Nevertheless, book reading seems to be a rarity in some societies. Although reading is beneficial, the book market is not flourishing in many countries, including Romania. The present paper sets a framework for developing marketing strategies that could be used by Romanian publishers to attract more readers. The methodology comprises two parts. A first section is dedicated to the Romanian book market. Investigating its specificity helps us pinpoint the references for successful marketing strategies. The second part is based on the analysis of the scarce literature on marketing in the book industry in order to identify key aspects and vulnerabilities of marketing strategy in this sector.